2020
DOI: 10.1186/s12864-020-07254-x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a quantitative trait loci (QTL) associated with ammonia tolerance in the Pacific white shrimp (Litopenaeus vannamei)

Abstract: Background Ammonia is one of the most common toxicological environment factors affecting shrimp health. Although ammonia tolerance in shrimp is closely related to successful industrial production, few genetic studies of this trait are available. Results In this study, we constructed a high-density genetic map of the Pacific white shrimp (Litopenaeus vannamei) using specific length amplified fragment sequencing (SLAF-seq). The constructed genetic ma… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 66 publications
1
4
0
Order By: Relevance
“…A number of SNPs significantly associated with ammonia nitrogen tolerance were identified by using MLM, FarmCPU and Blink models. However, the p -value of these SNPs is relatively low, which could confirm previous speculations that ammonia nitrogen tolerance is highly polygenic and may be controlled by many genes with moderate to low effects ( Lu et al, 2016 ; Zeng et al, 2020 ).…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…A number of SNPs significantly associated with ammonia nitrogen tolerance were identified by using MLM, FarmCPU and Blink models. However, the p -value of these SNPs is relatively low, which could confirm previous speculations that ammonia nitrogen tolerance is highly polygenic and may be controlled by many genes with moderate to low effects ( Lu et al, 2016 ; Zeng et al, 2020 ).…”
Section: Discussionsupporting
confidence: 85%
“…Quantitative trait loci (QTL) linkage mapping is an essential method for identifying relevant genes. Zeng et al (2020) constructed a high-density genetic map of L. vannamei and mapped a QTL associated with ammonia nitrogen tolerance. Due to limitations of marker density, QTL analysis only identified one gene, LOC113809108, annotated as the ATP synthase g subunit.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…U. unicinctus , L. vannamei , and C. teleta are three typical pollutant-tolerant benthos that live in the intertidal zone. Among them, L. vannamei was reported to be resistant to a variety of pollutants, including nitrite [ 43 ], ammonia [ 44 ], sulfide [ 21 ], etc. C. teleta is a sediment-dwelling marine polychaete that is described as a pollution indicator species and is often found in disturbed or stressed organically and sulfide-enriched environments [ 45 , 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…Ammonia nitrogen is commonly considered the primary factor that can rapidly cause increased shrimp mortality. It was reported that the 96 h LC 50 of TAN in the adult black tiger shrimp Penaeus monodon was 65 mg/L [35], and the 72 h LC 50 of TAN in the adult Pacific shrimp was 345.94 mg/L [36]. Furthermore, our previous study demonstrated that the red swamp crayfish Procambarus clarkii with a larger size exhibited a higher and stronger antioxidant capacity, thus exerting a higher tolerance to ammonia stress [37].…”
Section: Acute Toxic Effects Of Ammonia Nitrogen On Shrimpmentioning
confidence: 88%